Dispute over Customary Land of the Bodi Sapik Clan, Certified Without the Permission of the Mamak Kapalo Waris and Its Settlement in Jorong Baruah, Tanah Datar - Rahmi Murniwati; Nanda Utama; Reza Wahyudi (Ekasakti Journal of Law and Justice, 2024)
Land disputes arise from conflicts of interest over land. Communal customary land is one type of land that is often disputed. One such dispute over communal customary land belonging to the Bodi Sapik clan occurred in Jorong Baruah, Nagari Padang Magek, Tanah Datar Regency. In this case, the communal customary land was certified without the permission of the head heir. West Sumatra Regional Regulation No. 7 of 2023 on Communal Customary Land states that the head heir is the leader of the communal customary land. Furthermore, Article 13 stipulates that the management and utilization of communal customary land is carried out by the head heir based on consensus with the clan members. Therefore, a study is needed with the following research questions: 1) Why did the defendant not seek prior permission from the head heir before certifying the Bodi Sapik clan's communal customary land? 2) How was the certification process of the Bodi Sapik clan's communal customary land carried out without the permission of the head heir in Jorong Baruah, Nagari Padang Magek, Tanah Datar Regency? 3) How was the dispute over the certification of the Bodi Sapik clan's communal customary land, which was carried out without the permission of the head heir in Jorong Baruah, Nagari Padang Magek, Tanah Datar Regency, resolved? This research uses an empirical juridical method with qualitative analysis. Based on the analysis and discussion, the results of this study show that the reason the defendant did not seek permission from the head heir when certifying the Bodi Sapik clan's communal customary land was because it was not the defendant who registered or certified the communal customary land, but rather the defendant's older brother, Jhond Kennedy, and because the defendant had not yet received his share of the inheritance and was trying to protect the inherited property. Meanwhile, the certification process of the Bodi Sapik clan's communal customary land in Jorong Baruah, Nagari Padang Magek, was carried out in 2000 when the defendant's older brother was the village head and there was a National Agrarian Operation Project (Prona) which authorized village governments to issue land ownership certificates (sporadik). This sporadik was used as the basis for land registration (issuance of a communal customary land certificate) at the Tanah Datar Regency Land Agency office. Furthermore, the dispute over the Bodi Sapik clan's communal customary land was resolved through negotiation, followed by mediation at the Tanah Datar Police Station, Batusangkar District Court, and finally at the Padang State Administrative Court.